PROCEDURE FOR GRANTING MICRO CREDIT (CREATION) AT PT PEGADAIAN (PERSERO) PELITA MAKASSAR BRANCH - Imran Tahalua (Jurnal Ilmu Manajemen Profitability, 2021)
The objectivies of the research were to find out kind evaluate the procedure of providing Micro Credit program (KREASI) at PT Pegadaian (Persero) Branch Pelita Makassar. The research was analysed descriptive qualitatively, the data were collected through observations and interviewing. This research was conducted in April to May 2020. The result of the research showed that the procedure of providing Micro Credit program (KREASI) at PT Pegadaian (Persero) Branch Pelita Makassar has been conducted well, starting with the introduction and approach of potential borrowers, the application stage for micro credit, identifying data. After identifying the data by the credit department, it can be deemed done or denied. The borrower then interviewing and the credit department reviewed the debtor directly. Afterwords, the credit department of analysis then analyzing the borrower’s credit to be given. If it is approved, the loan agreement (SPK) will be issued by the credit department and then make a credit agreement. If it is not approved, the credit department will issue a denial letter and return it to a customer.